نزاع العلماء في حكم ملازمة البيت للمرأة المسلمة سلفًا وخلفًا: Debate between Classical and Contemporary Scholars about the Ruling for a Muslim Woman on being confined at Home - Gazdar, Muhammad Amir; Al-Khairabadi, Mohammed Abullais (Journal of Al-Tamaddun, 2022)
This research is a comparative and analytical study that focuses on the ruling for a Muslim woman to be confined to her home. The researchers present the differences of opinion among classical and contemporary scholars on the issue, discuss their opinions along with comparison and analysis of the reasoning proffered and explains the intellectually convincing view on the issue. Furthermore, the researchers examine in depth the degrees of veracity and authenticity of aḥādīth of the Prophet (sws) that the scholars adduce in their contestations. In this regard, the researchers have used two approaches: the first is the comparative one and second is an analytical one. The researchers conclude that the opinion of the scholars who say that it is not permissible in Islam for Muslim women to leave their houses, go out for work and travel for their studies, is inauthentic and incorrect. This view is neither proven from the Qur’anic text, nor the Prophetic traditions. Moreover, it is against the common practice of the female companions of the Prophets (sws) at the time of his prophethood. Rather, it is verified that the Qur’anic injunction of staying at home was specific to the wives of the Prophet (sws) and it was imposed on them due to certain specific reasons. Therefore, it would not be appropriate at all to generalize this special directive and extend it to other ordinary Muslim women. It is not related to them. So, according to the intellectually convincing view of the scholars, it is permissible for Muslim women to go out of their houses for their daily life needs and necessities as the female companions of the Prophet used to do at the time of his prophethood. They just need to comply with the etiquette and provisions of the Qur’an. These include guarding the gaze from taking liberty, wearing decent and modest attire and avoiding exhibition of adornments worn on limbs other than the face, hands and feet on the occasions of male-female interaction, as is mentioned in Sūrah al-Nūr.